Application of Environmental Cost Budget in the Frame- work of Assessing Management Performance of PT. Union Foods in 2014-2017 - Suhartini, Suhartini; Winata, Suryadi; Widiyanto, Gregorius; Dama Yanti, Lia; Pratama, Rizky (Opción, 2019)
In the past decade, companies are required to take part in environmental pro- tection and be responsible for the social conditions of the communities around the company. The impact of production activities or services of a company can cause various environmental problems that harm various parties. So the purpose of this study is to determine the extent to which PT. Union Foods has carried out social and environmental responsibilities, to find out the form of application of environmental costs used by PT. Union Foods, and to find out the achievement of management performance in implementing environmental cost budgets. The type of research used in this study is descriptive research with a qualitative approach. The results of this study are: (a) PT. Union Foods has carried out social and environmental responsibilities in accordance with government regulations by implementing a waste management system in ac- cordance with its type and ensuring that the waste released into the environ- ment is not polluted, (b) Application of environmental cost budgets carried out by PT. Union Foods is compiling an environmental cost budget by classi- fying environmental costs into 4 categories: environmental prevention costs, environmental detection costs, internal environmental failure costs and exter- nal environmental failure costs and budgeting environmental costs of 18% of operational costs, (c) the management performance of PT. Union Foods is not good enough in implementing the budget and realization of environmental costs because in 3 years in a row it is not profitable for the company